Mentoring the Preparation of 4 Anti Programs (No Sexual Violence, No Bullying, No Intolerance, and No Corruption) for Elementary School Students at SDN BENDO 01 - Rarasati, Ida Putri; Rosyida, Desy Anindia; Putri, Erica Panggayuh (Edumedia Solution, 2025)
Community service activities as a form of implementation of the Tri Dharma of Higher Education which is carried out by involving lecturers, students and partner institutions. In this community service with the title